Gaps Manifesting in African Social Work: Eclectic Contexts in Africa - Simon Murote Kang’ethe (E-Journal of Humanities, Arts and Social Sciences)
Although the discipline of social work is pivotal in rejuvenating socio-economic welfare in ubiquitous corners of the world, it has paradoxically scored poorly in managing and leveraging welfare-based interventions in many African countries. The paper aims to discuss social work gaps in social welfare in some African countries. The paper used a review of the literature methodology that drew variegated literature from different research engines such as Google Scholar, EBSCOhost, Research Gate, and a few books and book chapters. The study has the following findings: poor professional conceptualisation, inadequate social workers in African countries, social work’s visibility deficits compared to its sister disciplines, absence of social workers in institutions of learning, poor policy and leadership involvement, social work gap in dealing with indigents, and social work suffers from gender stereotyping. The paper recommends that for social work to leverage its service delivery interventions, a collaboration between the forces of government NGOs and other social service professional bodies is necessary. The paper also advocates that the discipline be catapulted to its noble and honorable status as a very important discipline that enhances and turns around the service delivery process for a country’s citizens. The paper is very important for scholarship in that its content will add knowledge to the domain of social work by offering suggestions for leveraging social work service delivery, as well as informing policy and programmatic improvement in social work service delivery in the countries discussed.